Endoscopic Repair of Ischial Tuberosity Avulsion Fracture - Elizabeth C. Bond MB ChB, FRACS; Elizabeth J. Scott MD; Richard C. Mather MD, MBA (SAGE Publishing, 2024)
Background: The ischial tuberosity apophysis serves as an attachment site for the hamstring muscle complex in the pediatric pelvis. Once the apophysis begins to ossify around age 13 to 15 years, decreasing elasticity makes the physis the weakest part of the hamstring attachment to the pelvis. An avulsion injury of the hamstring muscle group in the adolescent therefore results in a fracture in the adolescent and is the functional equivalent to a 3-tendon proximal hamstring injury in an adult. Ischial tuberosity fractures have a higher rate of non-union than other pelvic apophyseal injuries. Endoscopic surgery offers the advantage of smaller incisions, reduced wound complications, and expedited recovery compared with an open procedure. Indications: Controversy exists over which fractures benefit from surgical fixation. Patients with an ischial tuberosity avulsion fracture that is displaced more than 20 mm or that remains symptomatic despite at least 3 months of conservative management are common indications for surgery. Technique Description: The patient is positioned in the prone position and under fluoroscopic guidance 2 endoscopic portals are created. The sciatic nerve is visualized, neurolysis performed, and then protected throughout the remainder of the case. The ischial tuberosity is located along with the avulsed apophysis and hamstring tendon. The bony surfaces are prepared. The fracture fragment is reduced and 3 partially threaded cannulated screws are percutaneously passed across the fracture. The interval between the semimembranosus and conjoined tendons was closed with a suture. Results: There are no results published specific to this technique. Outcome papers are lacking, but cohort studies show significant displacement increases risk for non-union. Displaced ischial tuberosity fractures are also thought to risk sciatic nerve irritation and decreased hamstring strength. Discussion/Conclusion: Recent advancements in periarticular endoscopic surgery of the hip have enabled this historically open procedure to be performed in a minimally invasive fashion. This technique achieves robust fixation of the avulsed fragment and the benefits of anatomic repair of the hamstring origin while avoiding the larger incision and soft tissue dissection required for an open procedure. In time, this technique may become standard of care much like other sports medicine procedures which have transitioned from open to arthroscopic with the development of suitable tools and techniques. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.